Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada Istiqomah Mart Kabupaten Tangerang - Reza Khairul Hadi; Asep Sulaeman; Komarudin Komarudin (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of product quality and service quality on customer satisfaction istiqomah martkabupaten tanggerang. The method used is quantitative. The sampling technique used the ancient roa formula and obtained a sample of 96 respondents. Data analysis used validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of this study are product quality has a significant effect on consumer satisfaction with a determination coefficient value of 43.1% and hypothesis testing obtained t count> t table or (3.328> 1.985). Service quality has a significant effect on customer satisfaction with a coefficient of determination of 43.1% and the hypothesis test is obtained t count > t table or (3.328> 1.985). Product quality and service quality simultaneously have a significant effect on customer satisfaction with the regression equation Y = 3.185 + 0.248X1 + 0.529X2. The coefficient of determination is 43.1% while the remaining 56.9% is influenced by other factors. Hypothesis testing obtained F count > F table or (35.163> 2.700).